The modulatory effects of Lonicera caerulea L. extract and omega-3 on sarcopenia via regulating PI3K and FOXO signaling pathways in rats - Radwa Wahid Mohamed; Nourhan Gamal El-Rahmany (Shahrekord University of Medical Sciences, 2024)
Introduction: Sarcopenia is an inflammatory disease caused by a disruption of muscle homeostasis. Lonicera caerulea L. (Haskap berry) (HB) extract and omega-3 (ω−3) possess antioxidant and anti-inflammatory activities. This study assesses the potential ameliorating effects of HB extract and ω−3 supplementation on dexamethasone (DEXA)-induced sarcopenia. Methods: Rats were divided into five groups; the negative control group was injected with saline (i.p.); groups 2, 3, 4, and 5 were injected with DEXA (2 mg/kg/d, i.p.); groups 3 and 4 also received 400 mg/kg/d and 100 mg/kg/d of HB extract and ω−3, respectively, while group 5 received both treatments daily for 21 days. The ameliorative effects of treatments were investigated by measuring lysosomal proteolytic enzyme cathepsin activity, phosphatidylinositol 3 kinase (PI3K) activity, nuclear factor kappa beta (NF-κB) level, and heme oxygenase-1 (HO-1) activity. The gene expression levels of muscle ring-finger protein (MuRF) and forkhead box O (FOXO) transcription factor were also evaluated. Biochemical and histological examinations were done on muscle tissues. Results: DEXA caused a significant elevation (P<0.05) in NF-κβ level and cathepsin activity in muscle tissue. Also, it significantly upregulated the muscle atrophy markers. Meanwhile, PI3K and HO-1 activities were significantly reduced. HB extract and ω−3 administration significantly (P≤0.05) reversed these effects and downregulated the mRNA expression levels of MuRF and FOXO. Also, the histopathological examination confirmed these results. Conclusion: The current study proved the ameliorative effects of HB extract and ω−3 on sarcopenia parameters. Therefore, they might be potential therapeutic agents for myopathy/sarcopenia.